In-situ preparation method of copper-based halide scintillator film
The copper-based halide scintillator film was prepared in situ by scraping the method, which solved the problem of long time periods and easy agglomeration of crystal powders during the traditional preparation process, and achieved a copper-based halide scintillator film with high stability and excellent optical properties. Suitable for X-ray detection.
Patent Information
- Application Number
- CN202411455761.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2024-12-13
AI Technical Summary
During the preparation process of traditional copper-based halide materials, the time period is long and the crystal powder is prone to agglomeration, resulting in poor imaging quality and it is difficult to achieve high scintillation performance and high uniformity at the same time.
Copper-based halide scintillator film was prepared in situ by scraping coating. By dissolving cuprous iodide and methyltriphenylphosphorus iodide in a mixed solvent, and adding polymethyl methacrylate, scraping through a coating machine Apply on a glass substrate, dry and cure, forming copper-based halide nanocrystals growing evenly in polymethyl methacrylate.
It realizes the preparation of copper-based halide scintillator films with simple operation, short cycle and low cost. It has high stability, low toxicity, excellent optical properties and rich earth elements, and is suitable for X-ray detection applications.
Smart Images

Figure CN119119536A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of scintillator films, and in particular to an in-situ preparation method of a copper-based halide scintillator film. Background Art
[0002] In recent years, metal halide materials have attracted extensive attention in the field of radiation detection due to their excellent optical properties, good stability and solution preparation. Traditional lead-based halide materials are considered to be emerging X-ray detection materials due to their strong X-ray absorption ability, high photoluminescence quantum yield and fast response time. However, the toxicity, self-absorption and low environmental stability of lead limit their practical applications. In contrast, zero-dimensional copper-based organic-inorganic hybrid halide materials have attracted increasing attention in the optoelectronic field due to their advantages such as high fluorescence quantum efficiency, environmental friendliness and high stability, especially in the fields of light-emitting diodes, photodetectors and X-ray imaging, showing great application potential.
[0003] A Chinese patent with authorization announcement number CN114031506B discloses a method for preparing a novel copper-based halogen perovskite phosphor, which is characterized by comprising the following steps: (1) adding a certain amount of MACl, CuCl powder and H3PO2 solution to a certain amount of DMF solution at room temperature, heating and stirring, and stopping heating and stirring after complete dissolution, filtering and standby; (2) vacuum drying the obtained solution in a vacuum drying oven, washing the obtained white powder with n-hexane, and then continuing to dry in a vacuum drying oven to obtain white crystals, namely MA2CuCl3 single crystals; in step (1), the molar ratio of MACl to CuCl powder is 2:1~4:1.
[0004] The above-mentioned prior art solutions have the following defects: the time cycle for preparing metal halides is usually long, and during the preparation process, the crystal powder is prone to agglomeration in the polymer, resulting in poor imaging quality. Therefore, the traditional two-step method is difficult to achieve high scintillation performance and high uniformity at the same time. In order to improve the problems such as low film scintillation performance caused by crystal powder agglomeration during the preparation of scintillator films by the traditional two-step method, the in-situ preparation of copper-based halide scintillator films has attracted widespread attention. In-situ prepared copper-based halide scintillator films usually have higher uniformity and wet-heat stability. Therefore, we propose a method for preparing copper-based halide scintillator films with a simple preparation process, short cycle and low cost, which is considered to be an important research direction for the industrial application of new scintillator films. Summary of the invention
[0005] The problem to be solved by the present invention is to provide an in-situ preparation method of a copper-based halide scintillator film in view of the above-mentioned deficiencies in the prior art. The method prepares the copper-based halide scintillator film in-situ by a scraping method, which has the advantages of simple operation, short cycle, low cost and good film stability.
[0006] The above-mentioned object of the present invention is achieved through the following technical solutions: An in-situ preparation method of a copper-based halide scintillator film comprises the following steps: S1: Cuprous iodide (CuI) and methyltriphenylphosphonium iodide (C 19 H 18 IP) is dissolved in a mixed solvent, and polymethyl methacrylate (PMMA) is added and continued to dissolve to obtain a precursor solution; S2: The precursor solution obtained in S1 is coated on a glass substrate by a coating machine, and then dried and solidified to form copper-based halide nanocrystals ((C 19 H 18 P)2CuI3 NCs) were uniformly grown in polymethyl methacrylate (PMMA), and after curing, a copper-based halide scintillator film (C 19 H 18 P)2CuI3@PMMA).
[0007] Furthermore, in the S1, the usage ratio of cuprous iodide, methyltriphenylphosphonium iodide, polymethyl methacrylate, and the mixed solvent is 2.00 mmol: 3.50-4.50 mmol: 1.50-2.50 g: 6.10-6.20 mL.
[0008] Furthermore, in the S1, the mixed solvent is N,N-dimethylformamide (DMF) and hypophosphorous acid (H3PO2).
[0009] Furthermore, in the S1, the volume ratio of N,N-dimethylformamide to hypophosphorous acid is 6.00:0.10-0.20.
[0010] Furthermore, in S1, the heating temperature for dissolution is 60-80° C., and the stirring speed is 360-460 r / min.
[0011] Furthermore, in S2, a 200 mm*100 mm thin layer of glass is pre-selected as a glass substrate, and after the surface of the glass substrate is cleaned with deionized water and ethanol in sequence, the glass substrate is preheated at 60-80° C. for 5-10 min.
[0012] Furthermore, in S2, after adjusting the slit distance between the coating end of the coating machine and the glass substrate, the precursor solution is dripped into the slit, and the coating end of the coating machine moves at a uniform speed from one end of the glass substrate to the other end to obtain a layer of wet copper-based halide film.
[0013] Furthermore, in S2, the slit distance is 200-300 μm, the amount of the precursor solution is 1.5-3.0 mL, and the moving speed of the coating end of the coating machine is 4-10 cm / s.
[0014] Furthermore, in S2, the drying and curing temperature is 60-80°C and the time is 3-6 hours.
[0015] Furthermore, in the S2, the thickness of the copper-based halide scintillator film is 80-120 μm.
[0016] In summary, the beneficial technical effects of the present invention are: 1. The in-situ preparation method of copper-based halide thin film adopted in the present invention has low preparation cost, simple process, non-toxic and harmless, can be prepared by low-temperature solution method, and has a short preparation cycle; at the same time, compared with other scintillating crystals, copper-based halide has the characteristics of high emission stability, low toxicity, economic and environmental protection, and rich earth element composition; 2. The copper-based halide film prepared by the present invention has a smooth surface, uniform texture, good flexibility, easy-to-control thickness and size, a certain transmittance, and excellent optical properties, a large Stokes shift, and is suitable for applications in the direction of X-ray detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a flow chart of the method provided in Example 1 of the present invention.
[0018] Figure 2 It is a scanning electron microscope and energy spectrum diagram of the copper-based halide scintillator film of Example 2 of the present invention.
[0019] Figure 3 It is the excitation and fluorescence spectrum diagram of the copper-based halide scintillator film of Example 3 of the present invention.
[0020] Figure 4 This is an X-ray diffraction pattern of the copper-based halide scintillator film of Example 4 of the present invention. DETAILED DESCRIPTION
[0021] In order to make the technical means, creative features, objectives and functions achieved by the present invention clearer and easier to understand, the present invention is further explained below in conjunction with the accompanying drawings and specific implementation methods. Example
[0022] Example 1: Reference Figure 1 , is an in-situ preparation method of a copper-based halide scintillator film disclosed in the present invention, comprising the following steps: S1: Cuprous iodide (CuI) and methyltriphenylphosphonium iodide (C 19 H 18 IP) is dissolved in a mixed solvent, and polymethyl methacrylate (PMMA) is added and continued to dissolve to obtain a precursor solution; S2 applies the precursor solution obtained in S1 to the glass substrate through a coating machine, and then dries and solidifies it to form copper-based halide nanocrystals ((C 19 H 18 P)2CuI3 NCs) were uniformly grown in polymethyl methacrylate (PMMA), and after curing, a copper-based halide scintillator film (C 19 H 18 P)2CuI3@PMMA).
[0023] Embodiment 2: An in-situ preparation method of a copper-based halide scintillator thin film disclosed in the present invention is different from Embodiment 1 in that it comprises the following steps: S1 firstly mix 2.00mmol of cuprous iodide (CuI) and 4.00mmol of methyltriphenylphosphonium iodide (C 19 H 18 IP) was added into a mixed solvent of 6.00 mL N,N-dimethylformamide (DMF) and 150 μL hypophosphorous acid (H3PO2), and magnetically stirred at 450 r / min for 3 h to dissolve, and then 2.00 g polymethyl methacrylate (PMMA) was added, and stirring was continued for 6 h under heating at 80 °C to obtain a precursor solution; S2 pre-selects a 200mm*100mm thin layer of glass as a glass substrate, and washes the surface of the glass substrate with deionized water and ethanol in turn, and then preheats the glass substrate at 80°C for 10 minutes; after adjusting the slit distance between the coating end of the coating machine and the glass substrate to 250μm, 2.0mL of the precursor solution obtained in S1 is dripped into the slit, and the coating end of the coating machine moves from one end of the glass substrate to the other end at a constant speed of 10cm / s, and is dried and cured at 60°C for 3h to make the copper-based halide nanocrystals ((C 19 H 18 P)2CuI3 NCs) were uniformly grown in polymethyl methacrylate (PMMA), and after curing, a 100 μm copper-based halide scintillator film ((C 19 H 18 P)2CuI3@PMMA).
[0024] Embodiment 3: An in-situ preparation method of a copper-based halide scintillator thin film disclosed in the present invention is different from Embodiment 1 in that it comprises the following steps: S1 firstly mix 2.00mmol cuprous iodide (CuI) and 3.50mmol methyltriphenylphosphonium iodide (C 19 H 18 IP) was added into a mixed solvent of 6.00 mL N,N-dimethylformamide (DMF) and 100 μL hypophosphorous acid (H3PO2), and magnetically stirred at 360 r / min for 3 h to dissolve, and then 1.50 g polymethyl methacrylate (PMMA) was added, and stirring was continued for 6 h under heating at 60 ° C to obtain a precursor solution; S2 pre-selects a 200mm*100mm thin layer of glass as a glass substrate, and washes the surface of the glass substrate with deionized water and ethanol in turn, and then preheats the glass substrate at 60°C for 5 minutes; after adjusting the slit distance between the coating end of the coating machine and the glass substrate to 200 μm, 1.5 mL of the precursor solution obtained in S1 is dripped into the slit, and the coating end of the coating machine moves from one end of the glass substrate to the other end at a constant speed of 4 cm / s, and is dried and cured at 60°C for 3 hours to make the copper-based halide nanocrystals ((C 19 H 18 P)2CuI3 NCs) were uniformly grown in polymethyl methacrylate (PMMA), and after curing, a copper-based halide scintillator film (C 19 H 18 P)2CuI3@PMMA).
[0025] Embodiment 4 is an in-situ preparation method of a copper-based halide scintillator thin film disclosed in the present invention, which is different from Embodiment 1 in that it comprises the following steps: S1 First, 2.00mmol of cuprous iodide (CuI) and 4.50mmol of methyltriphenylphosphonium iodide (C 19 H 18 IP) was added into a mixed solvent of 6.00 mL N,N-dimethylformamide (DMF) and 200 μL hypophosphorous acid (H3PO2), and magnetically stirred at 460 r / min for 3 h to dissolve, and then 2.50 g polymethyl methacrylate (PMMA) was added, and stirring was continued for 6 h under heating at 80 °C to obtain a precursor solution; S2 pre-selects a 200mm*100mm thin layer of glass as a glass substrate, and washes the surface of the glass substrate with deionized water and ethanol in turn, and then preheats the glass substrate at 60-80°C for 10 minutes; after adjusting the slit distance between the coating end of the coating machine and the glass substrate to 300 μm, 3.0 mL of the precursor solution obtained in S1 is dripped into the slit, and the coating end of the coating machine moves from one end of the glass substrate to the other end at a constant speed of 10 cm / s, and is dried and cured at 80°C for 6 hours to make the copper-based halide nanocrystals ((C 19 H 18P)2CuI3 NCs) were uniformly grown in polymethyl methacrylate (PMMA), and after curing, a copper-based halide scintillator film (C 19 H 18 P)2CuI3@PMMA). Comparative Example
[0026] Comparative Example 1 is an in-situ preparation method of a copper-based halide scintillator film disclosed in the present invention, which is different from Example 2 in that methyl ammonium chloride is used instead of methyl triphenyl phosphonium iodide.
[0027] Comparative Example 2 is an in-situ preparation method of a copper-based halide scintillator film disclosed in the present invention, which is different from Example 2 in that cuprous chloride is used instead of cuprous iodide.
[0028] Comparative Example 3 is an in-situ preparation method of a copper-based halide scintillator film disclosed in the present invention, which is different from Example 2 in that polymethyl methacrylate is not used.
[0029] Comparative Example 4 is an in-situ preparation method of a copper-based halide scintillator film disclosed in the present invention, which is different from Example 2 in that the molar ratio of cuprous iodide to methyltriphenylphosphonium iodide is 1:1.
[0030] Comparative Example 5 is an in-situ preparation method of a copper-based halide scintillator film disclosed in the present invention, which is different from Example 2 in that the molar ratio of cuprous iodide to methyltriphenylphosphonium iodide is 1:5.
[0031] Comparative Example 6 is an in-situ preparation method of a copper-based halide scintillator film disclosed in the present invention. The difference from Example 2 is that the thickness of the copper-based halide scintillator film is 50 μm.
[0032] Comparative Example 7 is an in-situ preparation method of a copper-based halide scintillator film disclosed in the present invention. The difference from Example 2 is that the thickness of the copper-based halide scintillator film is 150 μm. Performance testing
[0033] Experimental Example 1: The copper-based halide scintillator film prepared in Example 2 was subjected to structural characterization. Figures 2~4 shown.
[0034] The element distribution on the film surface was characterized by EDS, such as Figure 2 As shown in the figure, Cu, P and I elements are uniformly distributed in the entire scanning area. Therefore, we infer that copper-based halides (C 19 H 18 P)2CuI3 grows uniformly under the wrapping of PMMA polymer.
[0035] like Figure 3 The photoluminescence excitation (PLE) and photoluminescence (PL) spectra of the copper-based halide composite film are shown. The experiment was tested using a fluorescence spectrophotometer under 365nm excitation light, showing strong photoluminescence (PL) with an emission center of 492nm. In addition, the film has a large Stoke's shift and small self-absorption, which can reduce the degree of lateral light scattering.
[0036] The prepared copper-based halide composite film was crushed and subjected to XRD testing. The test results are as follows: Figure 4 As shown in the XRD pattern, it can be seen that (C 19 H 18 The diffraction peaks of (C)2CuI3@PMMA composite films 19 H 18 The simulated peak positions of P)2CuI3 correspond to each other, proving that (C 19 H 18 P)2CuI3 is generated without any other impurities.
[0037] Experimental Example 2: The copper-based halide scintillator films prepared in Example 2 and Comparative Examples 1 to 7 were subjected to film performance testing. The results are shown in Table 1.
[0038] The detection methods include X-ray diffractometer analysis (XRD); fluorescence spectrometer (PL), and absolute quantum yield tester. The mechanical properties test uses manual mechanical bending; the stability test is to place it in the air for 30 days or immerse it in water for 15 days, and then test the luminescence peak intensity.
[0039] Table 1 Structural testing Mechanical properties stability Optical performance Example 2 <![CDATA[The diffraction peaks of the product in the XRD pattern correspond to (C 19 H 18 P)2CuI3, and the intensity of the emission peak in the PL pattern is relatively strong]]> The surface is smooth and the texture is flexible. After being mechanically bent 100 times, it still maintains its original shape. There is no phase change in the air for 30 days, and the luminescence peak intensity remains unchanged; after immersion in water for 15 days, the PL peak intensity is still more than 90% of the original The photoluminescence quantum yield is 92.7% Comparative Example 1 There is no obvious diffraction peak in the XRD spectrum, indicating that no product is generated in situ The surface is rough, the texture is flexible, and it still maintains its original shape after mechanical bending. none Photoluminescence quantum yield 0 Comparative Example 2 There is no obvious diffraction peak in the XRD spectrum, indicating that no product is generated in situ The surface is rough, the texture is flexible, and it still maintains its original shape after mechanical bending. none Photoluminescence quantum yield 0 Comparative Example 3 <![CDATA[There is no diffraction peak corresponding to (C 19 H 18 P)2CuI3 in the XRD pattern, and the product has no emission peak]]> Cannot be cured into a film without adding polymethyl methacrylate none none Comparative Example 4 <![CDATA[There are no diffraction peaks corresponding to (C 19 H 18 P)2CuI3 in the XRD pattern, and the product has no emission peak]]> The surface is rough, the texture is flexible, and it still maintains its original shape after mechanical bending. none Photoluminescence quantum yield 0 Comparative Example 5 <![CDATA[There are no diffraction peaks corresponding to (C 19 H 18 P)2CuI3 in the XRD pattern, and the product has no emission peak]]> The surface is rough, the texture is flexible, and it still maintains its original shape after mechanical bending. none Photoluminescence quantum yield 0 Comparative Example 6 <![CDATA[The diffraction peaks of the product in the XRD pattern correspond to (C 19 H 18 P)2CuI3, and the intensity of the emission peak in the PL pattern is weak]]> Poor mechanical properties, rough surface, brittle texture, easy to tear after mechanical bending There is no phase change in the air for 30 days, and the luminescence peak intensity remains unchanged; after immersion in water for 15 days, the PL peak intensity is still more than 80% of the original The photoluminescence quantum yield is 35.39% Comparative Example 7 The product diffraction peak in the XRD spectrum is weak, and the luminescence peak intensity in the PL spectrum is weak Poor mechanical properties, rough surface, hard texture, easy to tear after bending There is no phase change in the air for 30 days, and the luminescence peak intensity remains unchanged; after immersion in water for 15 days, the PL peak intensity is still more than 80% of the original The photoluminescence quantum yield is 51.2% It can be seen from Table 1 that the XRD diffraction peaks of the product synthesized under the conditions of Example 2 are similar to (C 19 H 18 P)2CuI3 corresponds well, and has a strong luminescence peak intensity, as well as good mechanical properties and stability, proving that under the conditions of Example 2, a high-quality (C 19 H 18 P)2CuI3@PMMA composite film.
[0040] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. An in-situ preparation method for a copper-based halide scintillator thin film, Features: The following steps are included: S1: dissolving cuprous iodide and methyl triphenyl phosphonium iodide in a mixed solvent, and adding polymethyl methacrylate to continue dissolving to obtain a precursor solution; S2: coating the precursor solution obtained in S1 on a glass substrate by a coating machine, and drying and curing the solution, so that the copper-based halide nanocrystals are uniformly grown in the polymethyl methacrylate, and a copper-based halide scintillator film is obtained after curing.
2. The in-situ preparation method of a copper-based halide scintillator thin film according to claim 1, Features: In the S1, the usage ratio of cuprous iodide, methyltriphenylphosphonium iodide, polymethyl methacrylate, and the mixed solvent is 2.00 mmol: 3.50-4.50 mmol: 1.50-2.50 g: 6.10-6.20 mL.
3. The in-situ preparation method of a copper-based halide scintillator thin film according to claim 2, Features: In the S1, the mixed solvent is N,N-dimethylformamide and hypophosphorous acid.
4. The in-situ preparation method of a copper-based halide scintillator thin film according to claim 3, Features: In the S1, the volume ratio of N,N-dimethylformamide to hypophosphorous acid is 6.00:0.10-0.
20.
5. The in-situ preparation method of a copper-based halide scintillator thin film according to claim 1, Features: In the above S1, the heating temperature for dissolution is 60-80° C., and the stirring speed is 360-460 r / min.
6. The in-situ preparation method of a copper-based halide scintillator thin film according to claim 1, Features: In S2, a 200 mm*100 mm thin layer of glass is pre-selected as a glass substrate, and after the surface of the glass substrate is cleaned with deionized water and ethanol in sequence, the glass substrate is preheated at 60-80° C. for 5-10 min.
7. The in-situ preparation method of a copper-based halide scintillator thin film according to claim 1, Features: In S2, after adjusting the slit distance between the coating end of the coating machine and the glass substrate, the precursor solution is dripped into the slit, and the coating end of the coating machine moves uniformly from one end of the glass substrate to the other end to obtain a layer of wet copper-based halide film.
8. The in-situ preparation method of a copper-based halide scintillator thin film according to claim 7, Features: In the S2, the slit distance is 200-300 μm, the amount of the precursor solution is 1.5-3.0 mL, and the moving speed of the coating end of the coating machine is 4-10 cm / s.
9. The in-situ preparation method of a copper-based halide scintillator thin film according to claim 1, Features: In S2, the drying and curing temperature is 60-80°C and the time is 3-6 hours.
10. The in-situ preparation method of a copper-based halide scintillator thin film according to claim 1, Features: In the S2, the thickness of the copper-based halide scintillator film is 80-120 μm.
